Benzydamine induces apoptosis in astrocytes in vitro - Lima Feitosa, Mariana; Viana da Silva Costa, Deiziane; Maria Martins Teixeira, Izabell; SAMPAIO, TIAGO; Roseo Paula Pessoa Bezerra de Menezes, Ramon; Macedo Gaspar, Danielle; Costa Martins, Alice Maria; de Castro Brito, Gerly Anne; Florenço de Sousa, Francisca Cléa (Journal of Health & Biological Sciences, 2024)
Objective: the present work aims to evaluate the Benzydamine (BZD) effect on cell viability in astrocyte culture and investigated the death mechanism involved with its cytotoxic effect. Methods: in order to evaluate cell viability, the 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction assay was used, while flow cytometry was used to verify cell damage. The immunofluorescence assay was used to verify the expression of the marker’s caspase-8, caspase9 and p65 subunit of Factor nuclear kappa B (NFκB). A statistical analysis for MTT assay and Flow Cytometry were made using ANOVA with Dunett’s post-test; Student’s t-test was made for the Immunofluorescence. Significance was set at p < 0.05. Results: the MTT reduction assay showed that BZD (3.1 to 100 μg/mL) caused a decrease in astrocytes viability. The flow cytometry showed that the cytotoxic effect of BZD was caused by the activation of the apoptotic death pathway, evidenced by the externalization of phosphatidylserine. The immunofluorescence revealed an increase in caspase-8 expression and no alteration in caspase-9 expression, demonstrating that there was an activation of the extrinsic pathway of apoptosis. The mean inhibitory concentration (IC50) of BZD (26.13 μg/mL) also caused an increase in NFκB p65 expression. Conclusion: taken together, the results of the present study suggest that BZD has a cytotoxic effect on astrocyte cells, and this effect comes from its ability to activate the extrinsic apoptotic pathway.